Executive Summary: Ethics in Education Research - A context mapping report of the TEACH-er project - Quesada Pallarès, Carla; Contreras-Benítez, Allan; Ion, Georgetta; Ciraso-Calí, Anna; Sáchez-Martí, Angelina; Brennan, Aimie (Zenodo, 2025)
The Self-Developed Teacher Education Research Ethics Competency (TEACH-er) project is an eighteen-month Erasmus+ small-scale partnership (KA210-SCH) led by the Marino Institute of Education (MIE), Dublin, in collaboration with the Universitat Autònoma de Barcelona (UAB) and St Joseph’s Secondary School, Dublin. Funded under the Erasmus+ Partnerships in School Education (2025–2026), the initiative addresses a gap in professional learning for teacher-researchers. Teachers who undertake classroom-based research frequently do so without access to formal ethics training, advice or oversight. As practitioner inquiry and evidence-informed practice become increasingly central to teaching practice, educators encounter complex ethical dilemmas and would benefit from ethical guidance. The project team work with teachers to generate resources to enable teacher-researchers to assess their own skills, knowledge and needs with regards to education research ethics; to build the capacity of teachers to engage in classroom-based research in ways that are ethically sound in the absence of ethical oversight; and to produce resources which will be informed by the real-world unique ethical dilemmas facing teachers-as-researchers. This report is developed as part of Activity 2, entitled ERE Context Mapping, aiming at reviewing relevant scholarly literature, professional ethics oversight in other professions, and ethics policy and guidelines across the EU to generate an in-depth understanding of ERE competence for teacher research. While the term practitioner-researcher encompasses a broad range of professionals engaged in systematic reflection on their own practice, this report deliberately narrows its scope to teachers acting as researchers within school settings. Our aim is to explore the ethical dimensions that emerge when teachers investigate their own classrooms, including how they manage issues of consent, assent, student voice, confidentiality, anonymity, data analysis and reflexivity.
This item is the executive summary of a context mapping report produced within the TEACH-er project. The full report is forthcoming.
Keywords: ethics in education research; research ethics; TEACH-er project; Erasmus+; teachers-as-researchers; Education--Research--Moral and ethical aspects